Nivel de valoración de los docentes sobre el potencial de la Dramatización como técnica para el aprendizaje de la expresión y la Comprensión oral de los niños y niñas de cinco años de las Instituciones Educativas del Nivel Inicial del distrito de Rioja en el año 2008 - Chuquiano Revilla, Margarita (2009)
Language is the human being's exclusive instrument for which permits transmitting to us and to receive information through multiple resources as facial expressions, expressions, etc. verbal manner becomes indispensability the resource more importantly. Therefore, the human being from his life's first stages learns to get in touch with thanks to his compatibility midway and with the adult. In that connection improving the communicative capability he must owe the educational process's permanent action. Therefore , this work investigated the position valorativa of the teachers of the initial level on the dramatization as technique to increase the power of the expression's abilities; Having as objectives: Examining , establishing and comparing the evaluation levels of the teachers on the potential of the dramatization as technique in order to the expression's learning and the children's oral understanding. Theories come into question to understand the communication process: them first helped to tell us from learning the acquisition, get along well as acquisition of a completely accessible language, the second best he displays relation that he exists among a good oral understanding and he forms it of expressing oneself and finally, the theory curricular on the expression and oral understanding in the learning process. As to the dramatization as resource of expression, as learning and as communicative competition. He aspect the investigation's methodological, substantival and descriptive - level's fellow's investigation was elected; the population muestral was shaped for 50 teachers that they have in his care 5- years boys and girls in the urban area of Rioja's district. The 50 aftermaths The teaching respondents 37 is on top of the value And the remainder 50 What indicates the favorable attitude am placed underneath that value Level in accord: 70% on the average) On the evaluation of the teachers of the initial level of Rioja's district on the potential of the dramatization as technical didactics in order to the expression's learning and oral understanding of the 5- years boys and girls. Of them hypothesis presented a high level in the evaluation gains a firm hold on existent the teachers on the potential of the dramatization as technique in order to the expression's learning and the five - years boys and girl's oral understanding institutional educational of the initial level of Rioja's district in the year 2008.